ANALISIS REFOCUSING ANGGARAN SAAT CORONA PERSPEKTIF EKONOMI ISLAM - Siti Alina; Delmayuni Jasman; Alya Ardita Piliang (CV. Adiba Aisha Amira, 2024)
This research aims to find out how budget refocusing is implemented and the solution during Covid-19 from an Islamic perspective. When budget refocusing becomes a problem, many government programs are not realized, which has an impact on reducing economic growth and increasing financing in the health sector. Using descriptive qualitative research methods. Qualitative research is a method of research and understanding that is based on methods for studying social phenomena and human problems. The data used by the author is secondary data obtained from literature, which is relevant, namely journals, books, internet sources related to the impact of refocusing the budget during Corona Covid 19 from an Islamic perspective. The results of this research show that Zakat has an important role in the process of preventing an economic crisis. Zakat has a big impact on the revival of Islamic civilization apart from preventing a national economic crisis in a country that cannot be lost over time